Iron Heterogeneity in Early Active Multiple Sclerosis Lesions. Issue 3 (19th December 2020) - Tham, Mylyne; Frischer, Josa M.; Weigand, Stephen D.; Fitz‐Gibbon, Patrick D.; Webb, Samuel M.; Guo, Yong; Adiele, Reginald C.; Robinson, Christopher A.; Brück, Wolfgang; Lassmann, Hans; Furber, Kendra L.; Pushie, M. Jake; et al.
Abstract : Objective: Multiple sclerosis (MS) is a heterogeneous inflammatory demyelinating disease. Iron distribution is altered in MS patients' brains, suggesting iron liberation within active lesions amplifies demyelination and neurodegeneration. Whether the amount and distribution of iron are similar or different among different MS immunopatterns is currently unknown. Methods: We used synchrotron X‐ray fluorescence imaging, histology, and immunohistochemistry to compare the iron quantity and distribution between immunopattern II and III early active MS lesions. We analyzed archival autopsy and biopsy tissue from 21 MS patients. Results: Immunopattern II early active lesions contain 64% more iron (95% confidence interval [CI] = 17–127%, p = 0.004) than immunopattern III lesions, and 30% more iron than the surrounding periplaque white matter (95% CI = 3–64%, p = 0.03). Iron in immunopattern III lesions is 28% lower than in the periplaque white matter (95% CI = −40 to −14%, p < 0.001). When normalizing the iron content of early active lesions to that of surrounding periplaque white matter, the ratio is significantly higher in immunopattern II ( p < 0.001). Microfocused X‐ray fluorescence imaging shows that iron in immunopattern II lesions localizes to macrophages, whereas macrophages in immunopattern III lesions contain little iron. Interpretation: Iron distribution and content are heterogeneous in early active MS lesions. Iron accumulates in macrophages in immunopattern II, but not immunopattern III lesions. This heterogeneity in the two most common MS immunopatterns may be explained by different macrophage polarization, origin, or different demyelination mechanisms, and paves the way for developing new or using existing iron‐sensitive magnetic resonance imaging techniques to differentiate among immunopatterns in the general nonbiopsied MS patient population. ANN NEUROL 2021;89:498–510